Infrastructure and ops hour with Sam Newman. (O'Reilly Media, Inc., 2021)
Join us for a special conversation on distributed systems with Sam Newman and cloud native architecture pro Nicky Wrightson. Working on a huge scale means a whole different set of problems to solve while still striving to keep systems operable, cost-effective, and maintainable. Nicky and Sam will walk you through some of the challenges of working with distributed systems before discussing why operability should be a first-class concern when developing large distributed systems, how to reduce the support overhead needed for complex distributed systems, and more. Then they'll open the floor for questions. What you'll learn and how you can apply it Explore the origins of, need for, and challenges around distributed systems See what's coming next for infrastructure and ops This recording of a live event is for you because... You want the chance to ask Sam Newman and Nicky Wrightson your questions around distributed systems. You're looking for ways to improve your production environments. Recommended follow-up: Read (book) Scalability and Concurrency for Distributed Systems Read , second edition (book) Building Microservices Read (book) Designing Distributed Systems Read (report) Distributed Systems Observability.